2006
DOI: 10.1128/aem.00341-06
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Distinctions among Clinical and Environmental Strains of Vibrio vulnificus

Abstract: Vibrio vulnificus causes rare but frequently fatal septicemia associated with raw oyster consumption by persons with underlying hepatic or immune system dysfunction. The virulence potential of environmental reservoirs appears widely distributed, because most strains are virulent in animal models; however, several investigations recently demonstrated genetic divergence among strains from clinical versus environmental origin at independent genetic loci. The present study used PCR to screen DNA polymorphisms in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
55
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 51 publications
12
55
4
Order By: Relevance
“…Similarly, distances between isolates of biotype 3 were rather low (average genetic distance, 0.302 Ϯ 0.197) ( Table 4) compared to the high genetic distances (average, 0.820 Ϯ 0.201) found between isolates of biotypes 1 and 2 (Table 4), demonstrating the wide genetic diversity of the latter groups. These results are consistent with previous findings revealing the low level of diversity of biotype 3 compared to biotype 1 isolates (5,7,16). Furthermore, distributions of specific alleles across the three biotypes, tested as variations in repeat number, were found to be significantly different at 10 of the tested loci (P, Ͻ0.05 for nine loci) (see Table SA3 in the supplemental material).…”
Section: ϫ4supporting
confidence: 82%
“…Similarly, distances between isolates of biotype 3 were rather low (average genetic distance, 0.302 Ϯ 0.197) ( Table 4) compared to the high genetic distances (average, 0.820 Ϯ 0.201) found between isolates of biotypes 1 and 2 (Table 4), demonstrating the wide genetic diversity of the latter groups. These results are consistent with previous findings revealing the low level of diversity of biotype 3 compared to biotype 1 isolates (5,7,16). Furthermore, distributions of specific alleles across the three biotypes, tested as variations in repeat number, were found to be significantly different at 10 of the tested loci (P, Ͻ0.05 for nine loci) (see Table SA3 in the supplemental material).…”
Section: ϫ4supporting
confidence: 82%
“…Real-time PCR of the 16S rRNA (rrn) polymorphic variants identified three major types: A, B, and hybrid AB ribotypes (11,44,57). The rrn B type was predominantly associated with clinically isolated strains, and the A and AB types were associated with environmentally derived strains.…”
mentioning
confidence: 99%
“…DNA polymorphism at the vcg locus, detected by a simple PCR method, identified vcgC versus vcgE genotype strains predominantly associated with clinical or environmental isolation, respectively (48). vcg typing generally matched rrn typing (11,16,49). Bisharat et al (4,5) used multilocus sequence typing (MLST) of housekeeping genes to type 159 V. vulnificus strains and constructed an online database for V. vulnificus MLST (http://pubmlst.org /vvulnificus/).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Genotyping based on molecular techniques, such as Pulsed-field gel electrophoresis, ribotyping, RAPD-PCR, extragenomic palindromic DNA PCR (Arias et al 1998;Chatzidaki-Livanis et al 2006); multilocus sequence typing (Bier et al 2013;Bisharat et al 2005;Cohen et al 2007;Reynaud et al 2013) and comparative genome analysis (Morrison et al 2012) have shown that V. vulnificus populations could be divided into two genotypes, the C-or the E-type. The C-type has been correlated to clinical origin responsible for human infections, while the E-type to those isolated from environmental origin and considered non-pathogenic.…”
Section: Introductionmentioning
confidence: 99%